PENGARUH FAKTOR MODAL DAN TENAGA KERJA TERHADAP OUTPUT MARGINAL PADA PANDER JAYA MEBEL - St Asrah Jannah Shalehah; Abdul Muttalib; Nasrullah Nasrullah (Universitas Muhammadiyah Makassar, 2017)
This study aims to abtain answers to whether capital production and labor factors contribute to marginal’s output on the Pander Jaya Mebel. The sample used was 30 workers of Pander Jaya Mebel furniture. The type of research instruments used are questionnaires and documentation. Processing of research data is using descriptive statistics while the data analysis technique used is the Regression the with a significance level of 0.05. through data processing, the following results are obtained : production factor and labor contribute to changes output marginal of 5,687, The results of the regression analysis as a whole show R eruel to 0.733 which means that the production factor and labor have a strong influence that is equel to 73.3%. The variable that has the must influence on marginal output is the capital factor variable seen from the resylt of the t test which is carried out by the variable cons ant value of capital factor far below 0.05 that is equel to 0.001.